Involuntary admission legislation and human rights in Low and Middle Income Countries (LMICs) - Eby, Cassandra Elise (Global Health: Annual Review, 2019)
This study determined the extent to which involuntary admission legislation in LMICs meet international human rights standards by using the WHO Checklist on Mental Health Legislation. The findings of this analysis suggest that, in many cases, the laws do not fully protect the rights of individuals with mental disorders in the context of involuntary admission, according to WHO standards. 43% of all standards analyzed for the LMICs in this study were rated as “Adequately covered”, leaving 57% of the standards for involuntary admission as either “Covered to some extent” or “Not covered at all”.